Hubungan antara Tipe Kepribadian dengan Performansi Mengajar Guru TK dan RA - Ghufron, Muhammad Nur; Risnawita S, Rini (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
The aim of the present study was to determine the relationship betweenbig five personality and performance of teachers in the kindergarten and Islamickindergarten. The subjects of this study were teachers in the kindergarten andIslamic kindergarten Kudus. Samples (N=77) were collected through a conveniencesampling technique, and completed a questionnaire in the form of a scale. Theresults of the study showed that there was a positive significant relationshipbetween extraversion, openness to experience, agreeableness and performance ofteachers in the kindergarten and Islamic kindergarten and in contrast there was anegative significant relationship between neuroticism and conscientiousness andperformance of teachers in the kindergarten and Islamic kindergarten.